Business Model Innovation in the Digital Era: An IT Sector Perspective - Hira Shafqat; Sidra Ghulam Muhammad; Rimsha Shahid; Fasiha Batool; Alina Idrees; Ayesha Sadiqa (Indus Journal of Social Sciences, 2025)
Over the past decade, practitioners and researchers gave few attention to business model innovation (BMI). An actual business model (BM) gives the platform which clearly recognize the commercial enterprise principles like: how the revenue and costs estimates, how to create competitive business, what sort of troubles solving for whom, who are the first-class provider and clients, and the way the customer value could be produced. BMI is in particular readdress the prevailing BM and its recognition at the need of businesses patron, with this new fee proposition it offers betterment of employer technique, resources and profit formulation. Most of the authors display the commercial enterprise fashions and describe business model innovation in one-of-a-kind approaches. In crux, the primary objective is to analyze the business version innovation in Changing Environment of Businesses (Small medium Enterprises (SMEs) of Information Technology (IT) Sector) in Pakistan. Questionnaire revolved around outside and inner antecedents of BMI, novelty and scope of BMI and results of BMI.